THE IMPACT OF BULLYING ON TEACHING AND LEARNING: A CASE OF PRIMARY SCHOOLS OF MAMELODI, GAUTENG PROVINCE - Victoria Sophy Hlafane; Mashaba Ernest Khalabai; Maile Simeon; Nkomo Asaph Ntu Nkomo (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This article investigated the impact, causes, types of bullying and the measures employed by primary schools to curb bullying in the Tshwane South District in Mamelodi Township, Gauteng Province. The researchers wanted to learn more about the effects of bullying in underprivileged communities. Three schools took part in the study, which used a qualitative methodology. Semi-structured one-on-one interviews with instructors, learners, and school principals were used to gather data. There were fifteen participants in the study. The goal of the study was to learn more about the effects of bullying in underprivileged communities. Three schools took part in the study, which used a qualitative methodology. Semi-structured one-on-one interviews with instructors, learners, and school principals were used to gather data. Fifteen people participated in the study. The authors found that primary schools are challenged by the negative impact of bullying and that there are factors that cause bullying in primary schools. However, we conclude that there are several measures that can be used to curb bullying in primary schools.